CBMT-05. ROLE OF THE let7-eEF2K AXIS IN MYC-DRIVEN MEDULLOBLASTOMA ADAPTATION TO NUTRIENT DEPRIVATION. (5th November 2018) - Delaidelli, Alberto; Luca Negri, Gian; Sidhu, Simran; Remke, Marc; Pfister, Stefan; Taylor, Michael; Leprivier, Gabriel; Kool, Marcel; Sorensen, Poul
Abstract: BACKGROUND/OBJECTIVES: MYC amplification in medulloblastoma (MB) determines highly aggressive disease, underscoring an urgent need for novel therapies. Let-7 microRNAs (miRNAs) inhibit tumor progression and regulate metabolism by degrading several mRNAs, including MYC. Let-7 miRNAs are frequently repressed in cancer, including MYC-driven MB. We previously reported that eukaryotic Elongation Factor-2 Kinase (eEF2K) is a pivotal regulator of MYC-driven tumor adaptation to nutrient deprivation (ND). Our data indicate that the eEF2K 3' untranslated region (UTR) harbors a potential binding site for let-7 . In addition, eEF2K mRNA and let-7 miRNA expression negatively correlates in MB, suggesting regulation of the former by the latter. We therefore hypothesized that let-7 down-regulation induces eEF2K expression in MB, thereby supporting MYC-driven MB adaptation to ND and tumor progression. METHODS: Immunohistochemistry for eEF2K substrate (p-eEF2) was performed on MB tissue microarrays to link results with MYC expression and clinical outcome. Effects of eEF2K pharmacological inhibition on MB cell survival were evaluated in vitro by MTT assays. The ability of let-7 to degrade eEF2K mRNA was assessed by let-7 miRNAs transfection into MB cells, followed by RT-PCR and Western Blotting for eEF2K. Binding of let-7 to the eEF2K 3'UTR was validated by luciferase reporter assays. RESULTS: High eEF2K activity is linked to MYC over-expression and reduced survival in MB (p<0.05). Pharmacological inhibition of eEF2K significantly reduces survival of MYC -amplified MB cell lines under ND. Transfection let-7 miRNAs decreases eEF2K mRNA and protein levels (by ~40–50%) in MB cells. Down-regulation of luciferase activity by let-7 miRNAs is impaired upon mutation of the let-7 binding site on the eEF2K 3'UTR. CONCLUSIONS: Let-7 miRNAs degrade eEF2K mRNA, indicating that let-7 repression in MYC-driven MB is partially responsible for eEF2K increased levels and activity. Moreover, the let-7 -eEF2K axis represents a critical mechanism for MYC-driven MB adaptation to ND, constituting a promising therapeutic target.